Social Media Platforms with Adolescents' Knowledge and Attitudes towards Nutrition - Ibrahim, Muh. Siddik; Dahlia, Besse; Alwi, Juwitriani; Hayati, Nur; Saleh, Husna; Mardin, Muhammad Ikhwan (Sarana Ilmu Indonesia (salnesia), 2025)
Along with the development of technology, social media has become an integral part of adolescents' daily lives. This study is concerned with significant changes in the behavioral patterns of high school adolescents, particularly in terms of the consumption of information about nutrition. This study aimed to bridge the knowledge gap and understand the practical implications of the relationship between the use of social media platforms and knowledge and attitudes about nutrition among secondary school adolescents. This type of research is a cross-sectional study approach. This study was conducted in 2024 in the Buton district with a sample in the study of MAN 1 Buton students, using a purposive sampling technique of as many as 37 people. Data analysis used bivariate analysis to test the null hypothesis using the chi-square (X2) formula. This study showed a relationship between the use of social media with knowledge and attitudes about nutrition, with significant results on the frequency of length of use per day (p-value=0,05). In addition, there was also a significant relationship between the type of social media used and attitudes about nutrition (p-value=0,031). This study concludes that its findings have significant implications for health education, particularly in guiding the development of curricula that incorporate social media as an effective and contextually relevant platform for delivering nutrition education to adolescents.